Information needs and information-seeking behaviour related to prostate cancer - Kassianos, Angelos P. (My University, 2012)
This study will look at information needs and information-seeking behaviour of people who have prostate cancer as well as those significantly related to them. In total 146 (N = 146) respondents participated. Significant associations were found between diet as a perceived risk factor and diet as an information need after diagnosis for prostate cancer patients (β = 0.821, p < 0.001) and after realizing the risk of developing prostate cancer for those at risk (β = 0.801, p < 0.001). On the other hand diet (β = 0.283, p = 0.111), smoking (β = 0.271, p = 0.127), alcohol consumption (β = 0.124, p = 0.492) and exercise (β = 0.384, p = 0.028) were not significant predictors of lifestyle changes after diagnosis. We supported the hypothesis that diet as perceived risk factors predicts the need for information on diet after being diagnosed. However diet as a risk factor cannot explain the similar lifestyle change.